Calculation of equivalent magnetic permeability of ferromagnetic materials for modeling of three-dimensional eddy current fields - Karpushkin Sergey; Glebov Aleksey; Karpov Sergey (MATEC Web of Conferences, 2017)
The paper presents a method of calculating a constant value of magnetic permeability of ferromagnetic materials, equivalent to the basic magnetization curve by the criterion of real power. The proposed method makes it possible to use linear differential equations of the electromagnetic field in the analysis of three-dimensional fields of eddy currents in ferromagnetic materials, thus significantly reducing the calculation time. We propose a method of calculating the power of inductors using two-dimensional axisymmetric models. The scope of the proposed methods is limited to the case of placement of the inductor inside the ferromagnetic body.